Lipoprotein Cholesterol and Atherosclerosis - Kruth, H.S. (Current Molecular Medicine, 2001)
Progressive accumulation of cholesterol in the arterial wall causes atherosclerosis, the pathologic process underlying most heart attacks and strokes. Low density lipoprotein (LDL), the major carrier of blood cholesterol, has been implicated in the buildup of cholesterol in atherosclerotic plaques. Endothelial cells that line arteries function to transport LDL into the vessel wall. Models for the mechanism of cholesterol accumulation in atherosclerotic plaques emphasize increased LDL uptake into the vessel wall or increased retention of LDL that has entered the vessel wall. This article reviews the pathways of cholesterol entry and removal, the metabolism, and the physical changes of cholesterol in the vessel wall. How these processes are believed to contribute to cholesterol buildup in atherosclerotic plaques is discussed.
Keywords: Phospholipid (PL)